Prevalencia de la seropositividad a la leucosis bovina mediante la técnica diagnóstica de ELISA indirecta en hatos lecheros situados en Mesa de los Santos, Santander - Carrero Rojas, José Leonardo; Arevalo Martinez, Francisco; Tarazona, Adalberto; Cepeda, Boris Marcelo (Spei Domus, 2023)
The present research was carried out in cattle herds destined to milk production in the municipality of Mesa de los Santos, Santander, in order to establish the presence of Viral Bovine Leucosis (VBL) in the region, due to the fact that this disease has manifested huge impact, particularly over farms destined to milk production, causing high drops in production and, consequently enormous economic losses. During the project development, several stages were implemented. In the first stage, there was a selection of 75 rural lands which constitute the primary units of sampling; these farms are distributed in seven zones such as follows: La Esperanza, El Duende, Mesa Jeridas, La Navarra, Mesitas de San Javier, Carrizal and El Pilon. The second stage consisted in the random selection of the animals, regardless of age or sex; The blood samples were taken from coccygeal vein, using 20 caliber needles for vacutainer without anticoagulant. This blood samples were taken to the laboratory where condensed serum was obtained by standard method and the diagnostic technique used was Indirect ELISA antibodies. From 360 samples collected within the municipality, 263 presented antibodies titles superior to 0,55, indicating seroprevalence for VBL, for a total 73% seroprevalence. Negatives quantity were 94 samples with antibodies titles minor to 0,45, showing a 27% of negativity. At 6 Month to 1 year babies 54% reactivity was observed; at the of 1 to 2 years, it was 62%; from 2 to 3 years 75% and in the case of the 3 years elders, 87% respectively. There were 74 from 75 herds sampled in which reactivity was found within the evaluated herds, which represents reactivity’s 99%, although the herd is considered positive with one reactive animal.